2016
DOI: 10.1007/s40273-015-0366-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of First-Line Oral Therapies for Pulmonary Arterial Hypertension: A Modelling Study

Abstract: Background In recent years, a significant number of costly oral therapies have become available for the treatment of pulmonary arterial hypertension (PAH). Funding decisions for these therapies requires weighing up their effectiveness and costs. Objective The aim of this study was to assess the cost effectiveness of monotherapy with oral PAH-specific therapies versus supportive care as initial therapy for patients with functional class (FC) II and III PAH in Canada. Methods A cost-utility analysis, from the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 35 publications
(38 reference statements)
2
46
0
1
Order By: Relevance
“…While these agents can improve haemodynamics, quality of life, and functional capacity, the worldwide usage of these drugs is largely limited by their high price. In Canada, PAH medications cost between Can$881 (tadalafil) and Can$4,028 (amberisentan) per month (Coyle et al, 2016). In the United States, the cost for bosentan and epoprostenol can be as much as $25,000 and $35,000 per month, respectively (Wryobeck, Lippo, McLaughlin, Riba, & Rubenfire, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While these agents can improve haemodynamics, quality of life, and functional capacity, the worldwide usage of these drugs is largely limited by their high price. In Canada, PAH medications cost between Can$881 (tadalafil) and Can$4,028 (amberisentan) per month (Coyle et al, 2016). In the United States, the cost for bosentan and epoprostenol can be as much as $25,000 and $35,000 per month, respectively (Wryobeck, Lippo, McLaughlin, Riba, & Rubenfire, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it was found that bosentan more often than ambrisentan caused hepatotoxicity which resulted in drug withdrawal. Considering different frequency of adverse effects with each drug, Kathryn Coyle et al 2016 [19] calculated QALY 1 values for ambrisentan and bosentan using a Markov model. For a patient with functional class II and 1 QALY (Quality-adjusted life year) is a year of perfect health.…”
Section: Results Of Pharmacoeconomic Study Of the Use Of Volibris (Ammentioning
confidence: 99%
“…The first one was based on the assumption that the compared drugs are equally effective and, hence, implied the use of the cost-minimization method. The second scenario was based on the results of Kathryn Coyle et al 2016 [19] whose conclusions were indicative of significant differences in QALY between ambrisentan and bosentan owing to different safety profiles of the two drugs. According to the methodology of pharmacoeconomic analysis, in the second scenario we should use the cost-utility analysis.…”
Section: Results Of Pharmacoeconomic Study Of the Use Of Volibris (Ammentioning
confidence: 99%
“…Endothelial NO synthase expression, NO production and NO availability are substantially reduced in patients with PAH, 5,10 so the sGC stimulator may be effective in patients who have not sufficiently responded to a PDE5 inhibitor. [34][35][36] The recent open-label, uncontrolled, phase…”
Section: Sgc Stimulatormentioning
confidence: 99%
“…Treatment Response to PDE5 Inhibitor (RESPITE) study suggested that switching from PDE5 inhibitors to riociguat improved a range of clinical and haemodynamic endpoints in patients with PAH who have had an inadequate response to PDE5 inhibition. 34 Patients with PAH-systemic sclerosis (SSc) tend to have a worse prognosis than patients with idiopathic PAH, and have poorer responses to treatment and worse outcomes than those whose PAH is associated with other connective tissue diseases (CTDs). However, the long-term extension of the Pulmonary Arterial hyperTENsion sGC-stimulator Trial (PATENT-2) demonstrated the same survival at 2 years (93 %) for those with PAH-CTD and those with idiopathic or familial PAH who were receiving treatment with riociguat, despite more than half of the PAH-CTD patients having PAH-SSc.…”
Section: Iiib Riociguat Clinical Effects Studied In Patients With Insmentioning
confidence: 99%